Pendidikan Seks di Perguruan Tinggi: Apakah Pendidikan Seks Mempengaruhi Perilaku Seks dan Self-Esteem Pada Mahasiswa Generasi Z? - Septian Cahya Azhari; Ceceng Saepulmilah (Departement of Mathematics Education, 2023)
The violence and sexual harassment that occurs a lot in college makes sex education chosen as an alternative to preventive measures. Student sex behavior is one of the causes of sexual violence / harassment in addition to support from social media content that does not have editorialization. This study aims to investigate the relationship between students' understanding of sex education and sex behavior and self-esteem. SEM-PLS is used as a complex data analysis technique. The data collection technique uses a questionnaire filled out by 174 students of Siliwangi University by proportional random sampling. The results showed that there was a relationship between students' understanding of sex education and sex behavior and self-esteem.